Cold plumes trigger contamination of oceanic mantle wedges with continental crust-derived sediments: Evidence from chromitite zircon grains of eastern Cuban ophiolites - Proenza, J.; González-Jiménez, J.; Garcia-Casco, A.; Belousova, E.; Griffin, W.; Talavera, Cristina; Rojas-Agramonte, Y.; Aiglsperger, T.; Navarro-Ciurana, D.; Pujol-Solà, N.; Gervilla, F.; O'Reilly, S.; et al. (Elsevier, 2018)
© 2018 China University of Geosciences (Beijing) and Peking University. The origin of zircon grains, and other exotic minerals of typical crustal origin, in mantle-hosted ophiolitic chromitites are hotly debated. We report a population of zircon grains with ages ranging from Cretaceous (99 Ma) to Neoarchean (2750 Ma), separated from massive chromitite bodies hosted in the mantle section of the supra-subduction (SSZ)-type Mayarí-Baracoa Ophiolitic Belt in eastern Cuba. Most analyzed zircon grains (n = 20, 287 ± 3 Ma to 2750 ± 60 Ma) are older than the early Cretaceous age of the ophiolite body, show negative e Hf (t) (-26 to -0.6) and occasional inclusions of quartz, K-feldspar, biotite, and apatite that indicate derivation from a granitic continental crust. In contrast, 5 mainly rounded zircon grains (297 ± 5 Ma to 2126 ± 27 Ma) show positive e Hf (t) (+0.7 to +13.5) and occasional apatite inclusions, suggesting their possible crystallization from melts derived from juvenile (mantle) sources. Interestingly, younger zircon grains are mainly euhedral to subhedral crystals, whereas older zircon grains are predominantly rounded grains. A comparison of the ages and Hf isotopic compositions of the zircon grains with those of nearby exposed crustal terranes suggest that chromitite zircon grains are similar to those reported from terranes of Mexico and northern South America. Hence, chromitite zircon grains are interpreted as sedimentary-derived xenocrystic grains that were delivered into the mantle wedge beneath the Greater Antilles intra-oceanic volcanic arc by metasomatic fluids/melts during subduction processes. Thus, continental crust recycling by subduction could explain all populations of old xenocrystic zircon in Cretaceous mantle-hosted chromitites from eastern Cuba ophiolite. We integrate the results of this study with petrological-thermomechanical modeling and existing geodynamic models to propose that ancient zircon xenocrysts, with a wide spectrum of ages and Hf isotopic compositions, can be transferred to the mantle wedge above subducting slabs by cold plumes.